Wise leaders fostering employees’ speaking up behaviors: Developing and validating a measure of leader-expressed practical wisdom - Rego, A.; Meyer, M.; Reis Júnior, D.; Pina e Cunha, M. (Review of Managerial Science, 2025)
Practical wisdom, an essential component of leadership, has been approached mainly from a theoretical perspective. While there are barely any empirical studies on leaders’ practical wisdom, quantitative ones are even rarer, and no valid measure of a leader’s practical wisdom exists. Thus, our understanding of whether and how wise leaders influence their followers is limited. Inspired by Thomas Aquinas’ ideas on practical wisdom, we operationalize it as a tridimensional capacity of inquiring, judging, and acting in an emotionally regulated way, and develop and validate a corresponding measure of leader-expressed practical wisdom. To support our operationalization, we test how leader-expressed practical wisdom predicts employees’ speaking up behaviors via their psychological safety. Our rationale is that to make better decisions, wise leaders are receptive to employees’ views that address matters of concern and challenge the status quo with the intention of improving the situation – such a receptiveness being enabled by fostering employees’ psychological safety. Through a two-wave field study, a three-wave field study, and a vignette-based experiment carried out in three countries we obtain empirical support for that three-dimensional construct and show that leader-expressed practical wisdom predicts employees’ speaking up behaviors via their psychological safety.